Comparative study of pipelle and diagnostic curettage in obtaining endometrial sample in a woman with abnormal uterine bleeding - Hemasri, Deevi; Varalakshmi, Chinthareddy; Vineela, Myneedhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Though the gold standard method of assessing endometrium was hysteroscopic biopsy, various methods of endometrial sampling methods are available among which pipelle and dilatation and curettage are more commonly used in routine practice in endometrial assessment in evaluating abnormal uterine bleeding cases, the main objective of the study to compare the efficacy of pipelle and D and C in obtaining endometrial sample in AUB cases. Methods: A prospective study conducted on 200 AUB patients for a period of 1 year, first they underwent pipelle aspiration followed by dilatation and curettage in same setting. Results: In our study histopathology report was available in 170 out of 200 patients in pipelle. HPR was available in all cases of D and C. Out of 200 patients with pipelle, sufficient sample was obtained in 152 patients (76%) and 48 patients had insufficient samples (24%). Out of 48 insufficient samples with pipelle, HPR available in 18 cases. In remaining 30 cases sample was inadequate for the histopathologist to give comment. In those 30 cases in pipelle D and C was successful in collecting report. In diagnosing endometrial carcinoma and hyperplasia pipelle showed 100% sensitivity and specificity. Conclusions: Tissue diagnosis with pipelle apparatus can be quick and easy. Pipelle sampling can be utilized as a successful screening method in the outpatient department, having high specificity in identifying endometrial hyperplasia and carcinoma similar to D and C, as well as its cost-effectiveness, anesthetic morbidity, and intra and postoperative complications.